One‐Step Synthesis of Methanesulfonyloxymethyl Ketones via Gold‐Catalyzed Oxidation of Terminal Alkynes: A Combination of Ligand and Counter Anion Enables High Efficiency and a One‐Pot Synthesis of 2, 4‐Disubstituted Thiazoles. Issue 6 (27th March 2014) - Wu, Gongde; Zheng, Renhua; Nelson, Jonathan; Zhang, Liming
Abstract By using Mor‐DalPhos as the P, N‐bidentate ligand and mesylate as the counter ion, the resulting gold(I) complex catalyzes efficient oxidative transformations of various terminal alkynes into synthetically versatile methanesulfonyloxymethyl ketones. The mild reaction conditions and high efficiency permit the one‐pot synthesis of a range of valuable 2, 4‐disubstituted thiazoles by subjecting the resulting reaction mixture to a further condensation with thioamides under mild conditions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>